NEO EVOLUSI BUDAYA TARIAN PERANG DALAM TRADISI OJUNG DI DESA BLIMBING KECAMATAN KLABANG KABUPATEN BONDOWOSO - Fatihah, Lauhil; Dwi Riyanto, Edi (Jurnal Kajian Seni, 2024)
The Ojung tradition is a ritual tradition of requesting rainfall which is carried out by the Madurese and Pandalungan communities in East Java. When tracing the cultural genealogical roots of the tradition, it seems to remind people's collective memory of war dance movements from the classical period, but it is possible that the Ojung tradition is thought to have originated from a much older period of time, which is in prehistory. This study aims to determine the Neo Evolution of War Dance in the Ojung Tradition found in Blimbing Village, Klabang District, Bondowoso Regency. This research uses data collection methods in the form of field methods, namely case studies and uses data collection techniques, namely triangulation techniques. This research uses an analysis method in the form of an interpretative qualitative analysis method and uses a historical analysis model. The results of this study indicate that the Ojung Tradition which is still preserved in Blimbing Village, Klabang Subdistrict, Bondowoso Regency is an evolved culture rooted in the war dance of the Austronesian Nation which has undergone various processes of change and development while maintaining the main concept or core value of the tradition itself.